Specialist physician knowledge of chronic kidney disease: A comparison of internists and family physicians in West Africa - Antonios H. Tzamaloukas; Edith N. Okeke; Comfort A. Daniyam; Maxwell O. Akanbi; Musa Dankyau; Emmanuel I. Agaba; Patricia A. Agaba (AOSIS, 2012)
Background: Postgraduate training is aimed at equipping the trainee with the necessary skills to practise as an expert. Non-nephrology specialist physicians render the bulk of pre-end-stage renal disease care for patients with chronic kidney disease (CKD). We sought to ascertain the knowledge of CKD amongst non-nephrology specialist physicians who serve as trainers and examiners for a training, accrediting and certifying body in postgraduate medicine in West Africa. We also compared the knowledge of family physicians and non-nephrology internists.Methods: Self-administered questionnaires were distributed to non-nephrology specialist physicians who serve as examiners for the West African College of Physicians.Results: Only 19 (27.5%) of the respondents were aware of the Kidney Disease Outcomes Quality Initiatives guidelines for CKD management. Twenty five (36.2%) of the respondents had adequate knowledge of CKD. There was no significant difference in the proportion of family physicians and non-nephrology internists who had adequate knowledge of CKD (27.3% vs. 40.4% respectively; p = 0.28). Hypertension and diabetes mellitus were identified by all of the physicians as risk factors for CKD. Non-nephrology internists more frequently identified systemic lupus erythematosus as a risk factor for CKD, urinalysis with microscopy as a laboratory test for CKD evaluation, and bone disease as a complication of CKD than family physicians.Conclusion: There is a lack of adequate CKD knowledge amongst non-nephrology specialist physicians, since many of them are unaware of the CKD management guidelines. Educational efforts are needed to improve the knowledge of CKD amongst non-nephrology specialist physicians. Guidelines on CKD need to be widely disseminated amongst these physicians.Connaissances des spécialistes des maladies rénales chroniques : Une comparaison des internistes et des médecins de famille en Afrique de l'OuestContexte: La formation de troisième cycle vise à donner à l'étudiant les compétences nécessaires pour exercer en tant qu'expert. Les spécialistes hors néphrologie réalisent le gros de la prise en charge des maladies rénales en phase terminale pour les patients atteints de maladie rénale chronique (MRC). Nous avons cherché à déterminer les connaissances sur la MRC chez les spécialistes hors néphrologie qui sont formateurs et examinateurs pour une structure de formation, d'accréditation et de certification en médecine de troisième cycle en Afrique de l'Ouest. Nous avons également comparé les connaissances des médecins de famille et des internistes hors néphrologie.Méthodes: Des questionnaires auto-administrés ont été distribués à des spécialistes hors néphrologies qui occupaient des fonctions d'examinateurs pour le Collège ouest-africain des médecins.Résultats: Seulement 19 (27.5%) des sondés connaissaient les directives de la Kidney Disease Outcomes Quality Initiative pour la prise en charge de la MRC. Vingt-cinq (36.2%) d'entre eux disposaient de connaissances adéquates de la MRC. Aucune différence significative n'a été constatée dans la proportion de médecins de famille et d'internistes hors néphrologie qui avaient des connaissances adéquates de la MRC (27.3 %, contre 40.4 % respectivement; p = 0.28). L'hypertension et le diabète non insulinodépendant ont été identifiés par tous les médecins comme des facteurs de risque de la MRC. Les internistes hors néphrologie ont identifié plus fréquemment que les médecins de famille le lupus érythémateux disséminé comme un facteur de risque de la MRC, l'analyse d'urine au microscope comme test de laboratoire pour le dépistage de la MRC et la maladie osseuse comme une complication de la MRC.Conclusion: Les connaissances adéquates de la MRC sont insuffisantes chez les spécialistes hors néphrologie, puisque bon nombre ne connaissaient pas les directives de prise en charge de la MRC. Des efforts d'éducation sont nécessaires afin d'améliorer les connaissances de la MRC chez les spécialistes hors néphrologie. Les directives sur la MRC doivent être largement diffusées auprès de ces médecins.